Production Shifts and Upgrading in ASEAN Automotive Production Network: Case on Toyota-led Regional Value Chains - Riza Noer Arfani; Awan Setya Dewanta (IKAT: The Indonesian Journal of Southeast Asian Studies, 2018)
The study aims at exploring the phenomenon of regional production network in ASEAN (Association of Southeast Asian Nations) automotive sector/industry by employing a firm as well as macro-level analysis of data gathered through combining techniques between desk-study and a series of fieldwork. It examines patterns of production and manufacturing activities of leading Japanese automotive firms and their upgrading strategies as showcased by Toyota in an endeavor to cast the much-aspired ASEAN regional value chains (RVCs). Production shifts have been apparent as indicated in the trade patterns and trends in value added of key automotive products traded between Japan and its ASEAN partners during the past 25 years. The shifts have resulted in deepened localization of production and manufacturing activities of Japanese automotive lead firms in ASEAN countries. Such dynamic shifts, as shown especially in passenger cars and automotive parts and accessories, have further prompted upgrading efforts by the lead firms (along with their suppliers, subsidiaries, and local partners) which suggest the functioning RVCs. The upgrading embraces areas of upstream (on research, development, and design or RD&D), midstream (on production, manufacturing, and assembly) as well as downstream (on sales, marketing, and after-market) activities. Future policy outlook lays on the ability of firms and other related stakeholders in the region’s automotive sector/industry to team up in the upgrading activities and hence capture the value-added. ASEAN-Japan long and strong historical relations facilitate the enhanced collaborative automotive industrial development, particularly in the areas of technical capacity formation and supporting industries.